Implementasi Metode Rational Unified Process Pada Website PT. Cinta Kasih Pribadina - Rini, Arsia (Teknomatika, 2017)
PT Cinta Kasih Pribadina is a company that has a role in labor services, the importance of the role reflected on the ever-increasing need for labor services. Company profile website has an important role for a company that does service because it can present its vision, mission and company profile. In addition other benefits from the company profile website as a means that can shorten the meeting so that the client does not need to be asked in detail about the profile, vision, and mission of the company directly. Website development is done by the method of implementation of the Rational Unified Process (RUP). RUP is a method that uses the concept of object oriented, and have activities which focus on model development using the Unified models of Language (UML), have stages such as inception (beginning), elaboration (expansion or planning), construction, transition so very right in applying such methods on the website PT Cinta Kasih Pribadina.Keywords- RUP, website, company